2018
DOI: 10.1093/imrn/rnx319
|View full text |Cite
|
Sign up to set email alerts
|

Collections of Orbits of Hyperplane Type in Homogeneous Spaces, Homogeneous Dynamics, and Hyperkähler Geometry

Abstract: Consider the space M = O(p, q)/O(p) × O(q) of positive p-dimensional subspaces in a pseudo-Euclidean space V of signature (p, q), where p > 0, q > 1 and (p, q) = (1, 2), with integral structure:We prove that either R ⊥ is dense in M or Γ acts on R with finitely many orbits. This is used to prove that the squares of primitive classes giving the rational boundary of the Kähler cone (i.e. the classes of "negative" minimal rational curves) on a hyperkahler manifold X are bounded by a number which depends only on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Since the connected component of the identity of the monodromy group is a subgroup of the generic Mumford-Tate group of the family and the latter commutes with the defect group, the local system P(X/S) becomes constant after a finite base change S → S. Remark 4. 4 Conjecturally, the group P(X ) is trivial for any hyper-Kähler variety X with b 2 > 3. In fact, the triviality of the defect group is equivalent to the conjecture which says that MT(H * X ) = G mot (H * X ) (i.e.…”
Section: Is a Smooth And Projective Morphism To A Non-singular Connected Variety Smentioning
confidence: 99%
See 1 more Smart Citation
“…Since the connected component of the identity of the monodromy group is a subgroup of the generic Mumford-Tate group of the family and the latter commutes with the defect group, the local system P(X/S) becomes constant after a finite base change S → S. Remark 4. 4 Conjecturally, the group P(X ) is trivial for any hyper-Kähler variety X with b 2 > 3. In fact, the triviality of the defect group is equivalent to the conjecture which says that MT(H * X ) = G mot (H * X ) (i.e.…”
Section: Is a Smooth And Projective Morphism To A Non-singular Connected Variety Smentioning
confidence: 99%
“…In particular, if MBM(X ) = ∅ then Amp(X ) = NS + (X ). (ii) [4] Fix a deformation class of hyper-Kähler manifolds with b 2 ≥ 5. There exists a positive integer N , depending only on the deformation class, such that for any projective X of the given deformation type, every MBM class z on X satisfies −N < (z, z) < 0.…”
Section: Remark 52mentioning
confidence: 99%
“…The hyperkähler version of the so-called Morrison-Kawamata cone conjecture is proved recently by Amerik-Verbitsky ([AV17], [AV18]) based on their earlier work [AV15], using hyperbolic geometry and ergodic theory. Their result says that Aut(X) acts with finitely many orbits on the set of facets of the Kähler cone of X (see [AV16, Theorem 2.13 and the discussion after]).…”
Section: Cone Conjecturesmentioning
confidence: 99%
“…This approach is generalized in the present paper. In [AV3] it is shown that for each hyperkähler manifold M there exists N > 0, depending only on the deformation class of M , such that for all MBM classes v one has −N < q(v, v) < 0. In the present paper, we prove that the lattice H 2 (M, Z) of a hyperkähler manifold M satisfying b 2 (M ) 5 (this is believed to hold always, but no proof exists today) contains a primitive sublattice Λ ⊂ H 2 (M, Z) which does not represent numbers smaller than N (that is, for any nonzero v ∈ Λ, one has |q(v, v)| N ).…”
mentioning
confidence: 99%
“…To construct the maximal holonomy hyperkähler (that is, ISH) manifolds with no MBM classes, we recall from [AV4] that the MBM classes have bounded square: 0 > q(z) > −N . Therefore to exhibit a lattice with a parabolic automorphism it is sufficient to find one representing zero and not representing numbers between zero and −N .…”
mentioning
confidence: 99%